1997
DOI: 10.1183/09031936.97.10061224
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in Greenwich, UK: impact of the disease and current management practices

Abstract: A great deal of the care of patients with asthma takes place in general practices. The aim of the present study was to describe the impact of asthma in the community and to identify current asthma self-management practices.A two-part questionnaire survey was conducted in a random sample (23%; n= 24,398) of persons aged 16-50 yrs, registered with one of the 41 general practices in Greenwich, London, UK. The two parts were: a screening questionnaire identifying persons with current asthma (defined as waking with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…A higher use of ICS in females than in males was also found in a recent study in the UK and the Netherlands [7]. Like MARKS et al [25], the current authors found that a lower proportion of asthmatic smokers were using ICS compared with nonsmoking asthmatics. Lower usage of anti-asthmatics in smokers was also found in a previous investigation [26].…”
Section: Discussionsupporting
confidence: 80%
“…A higher use of ICS in females than in males was also found in a recent study in the UK and the Netherlands [7]. Like MARKS et al [25], the current authors found that a lower proportion of asthmatic smokers were using ICS compared with nonsmoking asthmatics. Lower usage of anti-asthmatics in smokers was also found in a previous investigation [26].…”
Section: Discussionsupporting
confidence: 80%
“…For sample size calculations it was assumed that the mean and standard deviation of the AQLQ score would be similar to that found in a study of asthmatic adults aged 20±44 yrs in Greenwich, also in South London, UK [18]. A sample size of 500 was chosen to detect a difference of 5 points on the original 80-point scale between current users and non-users with >90% power, assuming that 30% of subjects would be current users.…”
Section: Methodsmentioning
confidence: 99%
“…For most patients it is relatively mild although, for some, it leads to hospital admission or even death. [1][2][3] There is a broad consensus among health professionals that asthma symptoms can be at least partially prevented or controlled by regular use of inhaled steroids and by high-dose inhaled ß2-agonists during acute attacks in conjunction with short courses of oral steroids. [4][5][6] To prevent or relieve attacks quickly, increasing emphasis has been placed on self-management of asthma.…”
Section: Experience Of Asthmamentioning
confidence: 99%